David Adjaye - living spaces - Allison, Peter (Thames & Hudson, 2017)
Houses or domestic buildings are often among the first projects young architects design. For David Adjaye, such early commissions connected him to a rising generation of creators with whom he shared a range of sensibilities. His artistry, clever use of space, and inexpensive, unexpected materials resulted in many innovative and widely published houses. After fifteen years of practice and a raft of high-profile projects around the world--including the Smithsonian National Museum of African American History and Culture in Washington, DC--houses represent a smaller portion of Adjaye's work but are more potent as a result. Selecting projects that are challenging because of their sites, complexity, or architectural possibility, Adjaye has both expanded and sharpened his domestic design, taking it in new directions and to new locations.This monograph presents the fifteen finest and most recent examples, from Africa to Brooklyn, from desolate farmlands to urban jungles. Chronicled through informed descriptions and detailed and photographically rich visual documentation, the results testify to the importance of Adjaye's growing inventiveness and provide powerful ideas for residential architecture
Keywords: Adjaye, David -- Sir -- 1966-; Architektur; Bildband